2020
DOI: 10.1016/j.jrp.2020.104019
|View full text |Cite
|
Sign up to set email alerts
|

Predicting counterproductive work behavior: Do implicit motives have incremental validity beyond explicit traits?

Abstract: This study extends research on the link between personality and Counterproductive Work Behavior (CWB) by investigating whether the implicit Affiliation, Achievement, and Power motives contribute to the prediction of CWB beyond basic personality traits. Employees high in Affiliation, Achievement, and Power motives may disengage from CWB because it is not rewarding and thwarts goal attainment. In Study 1 (N = 263), we found that Affiliation predicted self-rated CWB beyond traits. In Study 2 (N = 121), we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 80 publications
0
19
0
1
Order By: Relevance
“…Typically described as individuals' relatively enduring preferences for specific classes of affectively charged incentives, implicit motives (IM) form long-term behavioral tendencies (Brunstein et al , 1998; Schultheiss and Brunstein, 2010). Research has found some evidence that IM relate to career and leadership outcomes (Apers et al , 2019; Delbecq et al , 2013; Lang et al , 2012; Runge et al , in press). Although most leadership scholars believe that motivation is an important element in leadership, research has not yet systematically investigated the role of gender in the IM of CEOs.…”
mentioning
confidence: 99%
“…Typically described as individuals' relatively enduring preferences for specific classes of affectively charged incentives, implicit motives (IM) form long-term behavioral tendencies (Brunstein et al , 1998; Schultheiss and Brunstein, 2010). Research has found some evidence that IM relate to career and leadership outcomes (Apers et al , 2019; Delbecq et al , 2013; Lang et al , 2012; Runge et al , in press). Although most leadership scholars believe that motivation is an important element in leadership, research has not yet systematically investigated the role of gender in the IM of CEOs.…”
mentioning
confidence: 99%
“…Survey measures of motives are explicit, as people consciously respond to items. Implicit motives must be captured by non-explicit measures (e.g., Bing et al, 2007 ; Payne and Gawronski, 2010 ; Lang et al, 2012 ; Runge and Lang, 2019 ; Runge et al, 2020 ). An example of such an implicit measure is the (Brief) Implicit Association Test, or (B)IAT, which Slabbinck and van Witteloostuijn (2020) used to develop an implicit PSM measure, revealing that the explicit survey measure of PSM is indeed very different from their implicit BIAT counterpart.…”
Section: Discussionmentioning
confidence: 99%
“…Motivation psychologists have noted that implicit motives function as a “hedonistic compass” (Runge et al, 2020, p. 7), leading to positive affective reactions when a goal-congruent incentive cue is present (Brunstein et al, 1998; Dufner et al, 2015; Schultheiss et al, 2009). In effect, aroused implicit motives lead to affective preferences (Kehr, 2004b; McClelland, 1985) that energize motivated behavior with respect to “hedonically charged goals” (Schultheiss & Köllner, 2021, p. 617; see also Berridge & Robinson, 2003; Bindra, 1978; Toates, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Employees high on the implicit power motive enjoy exerting influence and control over other people (McClelland & Burnham, 1976). They have a confident demeanor and appreciate public attention (McClelland & Watson, 1973), and they seek out opportunities to lead others and rise in the organizational hierarchy (McClelland & Boyatzis, 1982; McClelland & Burnham, 1976; Runge et al, 2020). People high on the implicit power motive prefer behaviors that involve gaining and maintaining prestige and social standing (Winter, 1973) and are likely to employ interpersonal control, persuasion, or impression management (Schultheiss & Brunstein, 2002; Winter, 1991).…”
Section: Follower Approach Motivation and Vision Pursuitmentioning
confidence: 99%